A Rare Case of Borderline Resectable Carcinosarcoma - Taffurelli, Giovanni; D’Ambra, Marielda; Pacilio, Carlo Alberto; Buscemi, Salvatore; Peri, Eugenia; Ricci, Claudio; Santini, Donatella; Pezzilli, Raffaele; Casadei, Riccardo; Minni, Francesco (JOP. Journal of the Pancreas, 2012)
Context Carcinosarcomas are neoplasms with mixed carcinomatous and sarcomatous elements, which rarely occur in the pancreas. Case report A 62-year-old man was admitted to our institute for the presence of intense abdominal pain, worsening of a type II diabetes and weight loss (10 kg in 3 months). The tumor markers (CEA, CA 19-9) were within normal range. A CT scan showed a large pancreatic head solid mass of about 5 cm in diameter, with central necrotic area with septa, peripheral contrast-enhancement and compression and dislocation of the superior mesenteric vein for a tract of 2.5 cm (G3). An US-guided percutaneous biopsy diagnosed a malignant, high grade spindle cells neoplasia with immunophenotypic pattern of sarcomas. Surgical approach was planned and a total pancreatectomy with vascular resection was performed. The vascular resection included a 8 cm tract of portal-mesenteric trunk and the reconstruction was performed using a donor’s femoral vein homograft. Pathological examination of the specimen showed a solid mass of 6 cm in diameter, with infiltration of the portal vein. Lymph nodes (n=48) were negative and the surgical margins were tumor-free. Microscopically the tumor was characterized by high grade, polymorphous, intensely desmin-positive spindle cells mixed with areas of moderately differentiated ductal adenocarcinoma. The remaining pancreatic gland was interested by a diffuse lympho-plasmacellular GEL-type acute pancreatitis. A final diagnosis of carcinosarcoma, pT3N0M0, was performed. The postoperative course was uneventful and the patient was discharged in post-operative day 14th. He is dead, 4 months after surgery. Conclusion In literature only 10 cases of pancreatic carcinosarcomas have been described All cases were treated surgically and they showed a poor prognosis (average 6 months) and a rapid recurrence of the disease as in our case.